Analisis dan Perbaikan Layanan Hotel Menggunakan Servqual dan Diagram Kartesius (Studi Kasus di Hotel Kombokarno) - Rindang Rayo Ranas; Agus Mansur (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2016)
AbstractThe purposes of this research is to analyze and suggest a service quality improvement in Kombokarno Hotel. This research used ServQual dimension variables that consist of tangible, reliability, responsiveness, assurance, and empathy as a dimensions of service quality. It used 144 guests of Kombokarno Hotel as a sample for the research. The result of the collected data then be tested based on it’s validation and reliability by using SPSS 16.0 software. The result of data processing shows the validity of each question variable in the questionnaire. Then the data be analyzed using ServQual method to see the Gap between hope and reality. Furthermore it is processed by Kartesius diagram to see what performance that need to be improved. The result of the researched shows that the cleanness of the hotel always in good term, the electronic utilities (lamp, AC, TV, etc), are functioned well, and the hotel’s building ‘good look’ became the most priority to improve the performance of service quality in the hotel.